Family screening in hypertrophic cardiomyopathy is underperformed, but can be improved by a specialised clinic. Issue 7 (July 2014) - Olaussen, A.; Beale, A.; Macciocca, I.; Ellims, A. H.
Abstract Background Hypertrophic cardiomyopathy (HCM) causes significant morbidity and sudden death. First‐degree relatives (FDR) of affected patients are at risk due to autosomal dominant inheritance. Guidelines recommend clinical screening, including echocardiography, for all FDR. Aim We sought to determine adherence to these guidelines, and whether a specialised HCM clinic improves screening rates. Method This 12‐month prospective follow‐up study obtained family pedigrees from all patients referred to the HCM Clinic @ The Alfred. The number of living FDR was determined, and whether they had previously been assessed by echocardiography. One year after a coordinated clinic‐based family screening approach was instituted, the number of additionally screened FDR was recorded. Results Three hundred and eight living FDR of 61 HCM patients were identified. Of these, echocardiography had previously been performed in only 80 (26%), yielding 13 (16%) additional cases of HCM. Twelve months after attendance at our clinic, 51 additional FDR were screened (64% improvement) and 8 new cases of HCM were identified. Conclusions Recommended family screening for HCM is underperformed, resulting in missed opportunities to detect subclinical HCM. A coordinated approach through a specialised HCM clinic improves screening rates, thus referral to such a service should be considered for all patients with HCM and their families.